Riddah dalam Perspektif Bahasa, Al-Qur’an dan Hadis (Studi Tentang Konsekuensi Hukum Riddah) - Roro Fatikhin (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
In Islamic studies, apostasy is still a matter that is also much discussed and the issue is always warm to be discussed time by time. so the conversation can always be interesting every time. The problem of riddah is basically a matter of belief and one's faith in a religion that he professes. The interesting one from this, that many Islamic Ulama give death punishment to the agent of riddah, but other Islamic Ulamarefuse that panishment, because Islam does not impose coercion on one's religion.This article is Library Research and tries to understand the consequences of the existing riddah law of the Qur'an and hadith. from this research can be concluded several things. the process of occurrence of riddah has occurred since a long time, and still happen time to time until now. There are two opinions relating to the consequences of the perpetrators of this riddah. first he was condemned to be death and second, he was not condemned to death. but when we see on the existing reality, it can be seen that the second opinion is that prevailed until now because that opinion matches in ths era.